2021
DOI: 10.3390/fermentation7040286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paper Mulberry Silage on the Growth Performance, Rumen Microbiota and Muscle Fatty Acid Composition in Hu Lambs

Abstract: Paper mulberry (Broussonetia papyrifera) is widely ensiled to feed sheep in southwestern China, as unconventional woody forage. Feeding lambs with paper mulberry silage (PMS) may improve certain feeding characteristics, thereby affecting the growth performance and meat quality. The aim of this study is to investigate the effects of four diets of PMS on growth performance, rumen microbial composition, and muscle fatty acids profile in Hu lambs. The results showed that 30% and 40% PMS increased the dry matter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
1
14
2
Order By: Relevance
“…Thus the relative abundance of Christensenellaceae was higher in centenarians 53 . The fermented complete feed significantly affected the microbial diversity in pig manure, with the most affected genera including Christensenellaceae_R-7_group , whose relative abundance was significantly reduced compared to the control group 55 . Yang’s studies indicated that the abundance of the Christensenellaceae_R-7_group was increased in the rumen as the content of n3-poly unsaturated fatty acids in longissimus dorsi muscle was increased 56 .…”
Section: Discussionmentioning
confidence: 96%
“…Thus the relative abundance of Christensenellaceae was higher in centenarians 53 . The fermented complete feed significantly affected the microbial diversity in pig manure, with the most affected genera including Christensenellaceae_R-7_group , whose relative abundance was significantly reduced compared to the control group 55 . Yang’s studies indicated that the abundance of the Christensenellaceae_R-7_group was increased in the rumen as the content of n3-poly unsaturated fatty acids in longissimus dorsi muscle was increased 56 .…”
Section: Discussionmentioning
confidence: 96%
“…Lactobacillus also were positively correlated with upregulated metabolites of sugars ( d -(+)-sucrose, d -allose, d -glucose, d -mannose, d -tagatose, d -talose) belonged to galactose metabolism, starch, and sucrose metabolism, carbohydrate digestion and absorption, but Christensenellaceae_R-7_group was just the opposite. Lactobacillus reuteri strains are widely used as probiotics to prevent and treat inflammatory bowel disease by modulating the host’s immune system . Feeding lambs with 40% paper mulberry silage could lead to a relatively high content of unsaturated fatty acids in longissimus dorsi muscle by increasing the relative abundance of Christensenellaceae_R-7_group in the rumen of Hu lambs .…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus reuteri strains are widely used as probiotics to prevent and treat inflammatory bowel disease by modulating the host's immune system. 48 Feeding lambs with 40% paper mulberry silage could lead to a relatively high content of unsaturated fatty acids in longissimus dorsi muscle by increasing the relative abundance of Christensenellaceae_R-7_group in the rumen of Hu lambs. 49 Those results also suggested feeding autoclaved ruminal solids promotes the levels of GLU and TG in lambs by altering the gut microbiota, which leads to glycolysis/ gluconeogenesis, but SRS reversed the process.…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, the proportion of Christensenellaceae R-7 group , f_ Ruminococcaceae/g_ and Ruminococcus 1 in the ileum was positively affected by the addition of coated trace elements. Christensenellaceae R-7 group play a pivotal role in the degradation of carbohydrates to acetate ( Morotomi et al, 2012 ), and the increase in their abundance was positively correlated with the improvement of growth performance and meat quality in Hu lambs ( Xiong et al, 2021 ). Both f_ Ruminococcaceae/g_ and Ruminococcus 1 belong to family Ruminococcaceae , which have great ability in the complex carbohydrates digestion to generate short chain fatty acids (SCFAs) ( Xie et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%